PROBATION: A HINDER OR A HELPER TO REHABILITATION AND DESISTANCE FROM CRIME? “PROBATION”: UM DANO OU UMA AJUDA À REABILITAÇÃO E À DESISTÊNCIA DO CRIME? - Amorim, Paula de Campos Mattar (Delictae Revista de Estudos Interdisciplinares sobre o Delito, 2018)
Considering the rise of community sanctions and measures in the criminal justice system, as well as the relevance of understanding the process of desistance from crime and rehabilitation, this study will demonstrate how probation can help individuals to stop offending and what are the obstacles to be tackled. Through researches and studies’ findings of Sue Rex, Shadd Maruna, Stephen Farral, Fergus McNeill and Deirdre Healy, probation’s role will be critically assessed in terms of quitting a criminal career and reinserting in society.